Enhancement in mechanical properties of polyamide 66-carbon fiber composites containing graphene oxide-carbon nanotube hybrid nanofillers synthesized through in situ interfacial polymerization. (August 2020) - Cho, Beom-Gon; Lee, Jung-Eun; Hwang, Sang-Ha; Han, Jong Hun; Chae, Han Gi; Park, Young-Bin
Highlights: PA66/CF/AGO-CNT composites were fabricated via in situ interfacial polymerization. The interphase-strengthened composites exhibited outstanding mechanical performances with optimal ratio between AGO and CNT. The energy-absrobing ability of the composites have been enhanced by 62% as compared to the control sample. Abstract: Polyamide 66 (PA66)/carbon fiber (CF) composites with acyl chloride-functionalized GO (AGO) and carbon nanotubes (CNTs) as hybrid fillers were prepared through in situ interfacial polymerization. The optimal ratio of AGO to CNTs in terms of hydrogen bonding in the composites was determined to be 2:1 via thermochemical analyses of the as-prepared PA66/AGO-CNT composites. The optimized hybrid filler-reinforced PA66/CF composites showed improvements in the interfacial shear strength, tensile strengh and storage modulus by 160, 136 and 300%, respectively, compared to the control sample, as well as high damping properties due to an enhanced transcrystalline interphase. The superior interfacial bonding between CF and PA66 is attributed to hydrogen bonding, enhanced dispersion, and the mechanical interlocking effect induced by AGO-CNT hybrids, which lead to effective energy absorption and load transfer.